Thesis by publication in education: An autoethnographic perspective for educational researchers - Merga, Margaret (Western Australian Institute for Educational Research Inc, 2015)
© 2015, Western Australian Institute for Educational Research Inc. All rights reserved. Despite its growing popularity, the thesis by publication is a less conventional format for doctoral dissertations in the field of education. The author successfully undertook a thesis by publication in education from 2012, to submission in 2014. This paper draws on both the literature in the field and the experiences of the author through an autoethnographic approach to explore some of the strengths and limitations of thesis by publication. Key reasons for adopting the thesis by publication mode are outlined, as well as consideration of which types of educational research are most suited to this mode. Institutional support mechanisms and personal attributes that can improve the likelihood of success in this mode are also explored, in addition to the challenges and issues that are particularly significant when producing a thesis by publication. A possible structure and organisation of a thesis by publication in education is also proposed, though this will be determined primarily by institutional policy. This paper will be of interest to prospective doctoral students and higher degree by research supervisors in education seeking to extend their knowledge and experience in this area.